Reactive Programming Paradigm for Development User Intrfaces - Bulgakova, O.S.; Zosimov, V.V. (Control systems & computers, 2019)
The article discusses the relevance of using the paradigm for user interfaces development. The essence of the reactive programming paradigm, its features and disadvantages are described. The technology of reactive programming ReactiveX is considered. Features of the reactive systems implementation are described as a result of an in-depth study of the main development tools and language structures. The reactive paradigm possibilities of reducing labor costs for building valid models, minimizing errors, and efficient and quick solution of the tasks are shown on the example of the application implementation. Мета статті. Дослідити актуальність використання парадигми реактивного програмування, як основи для розробки клієнтських інтерфейсів. Результати. В роботі розглянуто парадигму реактивного програмування, її відмінності від імперативного та функціонального програмування. Досліджена основна технологія, яка використовується сьогодні для створення додатків на основі реактивного програмування. На прикладі показано використання реактивної парадигми, яка дозволяє знизити трудовитрати на побудову валідних моделей, мінімізувати помилки, дозволяючи вирішувати поставлену задачу ефективно і швидко. Цель статьи. Исследовать актуальность использования парадигмы реактивного программирования, как основы для разработки клиентских интерфейсов. Результаты и выводы. В работе рассмотрена парадигма реактивного программирования и ее отличия от императивного и функционального программирования. Исследована основная технология, используемая сегодня для создания приложений на основе реактивного программирования. На примере показано использование реактивной парадигмы, которая позволяет снизить трудозатраты на построение валидных моделей, минимизировать ошибки, позволяя решать поставленную задачу эффективно и быстро.